2004
DOI: 10.2140/agt.2004.4.1083
|View full text |Cite
|
Sign up to set email alerts
|

Span of the Jones polynomial of an alternating virtual link

Abstract: For an oriented virtual link, L.H. Kauffman defined the fpolynomial (Jones polynomial). The supporting genus of a virtual link diagram is the minimal genus of a surface in which the diagram can be embedded. In this paper we show that the span of the f -polynomial of an alternating virtual link L is determined by the number of crossings of any alternating diagram of L and the supporting genus of the diagram. It is a generalization of Kauffman-Murasugi-Thistlethwaite's theorem. We also prove a similar result for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 10 publications
(32 reference statements)
1
31
0
Order By: Relevance
“…Source-sink orientations were originally introduced by Naoko Kamada [15] [16] and determine a version of checkerboard coloring for virtual knots. We note that the source-sink orientations we use can be regarded as a translation of the oriented chord diagrams of Oleg Viro [43].…”
Section: Source-sink Orientations and Cut Locimentioning
confidence: 99%
“…Source-sink orientations were originally introduced by Naoko Kamada [15] [16] and determine a version of checkerboard coloring for virtual knots. We note that the source-sink orientations we use can be regarded as a translation of the oriented chord diagrams of Oleg Viro [43].…”
Section: Source-sink Orientations and Cut Locimentioning
confidence: 99%
“…This notion was introduced by N. Kamada in [21,22], who showed that many classical results on knots and links can be extended to checkerboard colorable virtual links. A similar notion under the name of atom was studied by V. Manturov [30] following A. Fomenko [12].…”
Section: The Theorem From [7]mentioning
confidence: 99%
“…mod m almost classical) virtual link diagram of L. H. Dye introduced the notion of a cut point [3], which is an 'unoriented' cut point in our sense. The author [6] generalized the Kauffman-Murasugi-Thistlethwaite theorem ( [11,14,15]) on the span of the Jones polynomial of a classical link to checkerboard colorable and proper virtual links. Using cut points, H. Dye [4] further extended this result to virtual link diagrams that are not checkerboard colorable.…”
Section: Alexander Numberings and Cut Systemsmentioning
confidence: 99%